Language Learning Strategies Used by Awardees of Affirmation Scholarship in IELTS Preparation Class - Ika Tri Yunianika (Ahmad Dahlan Journal of English Studies, 2018)
The aim of this study is to find out the type of language learning strategies (LLSs) used by two groups of awardees for Affirmation Scholarship of Indonesia Endowment Fund for Education (LPDP) in IELTS preparation classes. Those group were preparing for the IELTS examination as the minimum requirement score for university entrance. The study attempts to investigate the particular pattern of LLS used by students with different gender, academic majors, and IELTS band score. The Strategy Inventory for Language Learning (Oxford, 1990) was used as an instrument to collect data from the two groups of IELTS preparation class. The results revealed that respondents tend to use meta-cognitive strategies as their main LLS with females being the more active users than males, while language major students used strategies more often than those who study in science and social studies. Participants who had good score in IELTS employed social strategies, besides affective strategies used by students who were less proficient in English. The findings have implications for students and teachers of IELTS class to utilize appropriate LLS in language learning.Â